Triglycerides Level and Body Mass Index in Type 2 Diabetes Mellitus Patients with Tuberculosis in an Indonesian Tertiary Hospital - Theresia Trishavena Yuanita Pramesty; Wahyunitisari, Manik Retno; Yudhawati, Resti; Setiabudi, Rebekah J.; Priyambodo, Djoko Agung (Universitas Airlangga, 2026)
Introduction: Type 2 Diabetes Mellitus (T2DM) is a chronic disease that can cause metabolic disturbances, includingdyslipidemia, characterized by elevated triglyceride levels. Patients with T2DM are also at higher risk of developingtuberculosis (TB) due to compromised immune function. Body Mass Index (BMI), which reflects nutritional status, mayinfluence triglyceride levels. In several studies, increasing BMI was accompanied by an increase in triglycerides. This studyaims to analyze the relationship between triglyceride levels and BMI in T2DM patients with TB in Dr. Soetomo GeneralAcademic Hospital, Surabaya, Indonesia, from 2021 to 2022. Methods: This study utilized secondary data from patients diagnosed with T2DM and TB between 2021 and 2022,respectively. Inclusion criteria were patients with complete medical records, including age, gender, cholesterol andtriglyceride levels, height, and weight, with 83 patients meeting these criteria. Statistical analysis was performed with oneway ANOVA for continuous variables, the Kruskal-Wallis test for non-homogeneous data, chi-square for categoricalvariables, and Pearson correlation for variable relationships. A p-value < 0.05 was considered statistically significant. Results: Triglyceride levels increased across all BMI categories, with values of 143.48 (57.83) for underweight, 173.74(75.74) for normal weight, and 183.80 (98.61) for overweight. Additionally, the correlation between BMI and triglycerideswas not significant (p=0.83), suggesting no meaningful association between these two variables in this study. Conclusion: The absence of differences in triglyceride levels in each BMI group is possible due to the use of triglyceridesfor the formation of granuloma triglyceride synthesis in T2DM with TB.